Ambulatory Behavior Map, Physical Activity and Biosignal Monitoring System - Murakami, D.; Makikawa, M. (Methods of Information in Medicine, 1997)
In this study, we have developed an ambulatory human behavior map and physical activity monitoring system. This was accomplished by equipping our portable digital biosignal memory device developed previously with GPS sensors and piezoresistive accelerometers. Using this new system, we can get a subject’s behavior map, and estimate his physical activities and posture changes in daily life.
Keywords: Ambulatory Monitoring; GPS; Behavior Map; Piezoresistive Accelerometer; Physical Activity; Posture Change